Pigmented squamous cell carcinoma: case report and importance of differential diagnosis - Patrícia Motta de Morais; Antônio Pedro Mendes Schettini; Jeanine Alvarenga Rocha; Renato Cândido da Silva Júnior (Sociedade Brasileira de Dermatologia, 2018)
Abstract: A few cases of pigmented squamous cell carcinoma affecting the skin and the ocular and oral mucosa of the elderly have been described in the literature. The disease manifests itself as papular and nodular erythematous or pigmented lesions. The main clinical differential diagnoses are pigmented basal cell carcinoma and melanoma. Histopathological examination is characterized by proliferation of atypical squamous cells with formation of horn pearls permeated by dendritic melanocytes. For this reason, a careful diagnosis is necessary to rule out other tumors that show melanin pigment. Surgical removal is the indicated treatment and the prognosis is similar to the classical squamous cell carcinoma. We report a case of pigmented squamous cell carcinoma with diagnosis confirmed by histological and immunohistochemical examinations.